2021
DOI: 10.34117/bjdv7n6-036
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de Bactérias Causadoras de Infecção Hospitalar Utilizando Fenotipagem Clássica / Identification of Hospital Infectious Bacteria Using Classical Phenotyping

Abstract: Este estudo teve como objetivo identificar os microrganismos presentes nas mãos da equipe multiprofissional alocados em Unidade de Terapia Intensiva (UTI), e seu papel nas IRAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Results previously published by our group [ 22 ] showed that 39.4% and 42.4% of S. haemolyticus species were resistant to penicillin G and oxacillin, respectively. S. auricularis exhibited values of 15.2% for both tested antibiotics and S. intermedius of 12.1% for both antibiotics.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Results previously published by our group [ 22 ] showed that 39.4% and 42.4% of S. haemolyticus species were resistant to penicillin G and oxacillin, respectively. S. auricularis exhibited values of 15.2% for both tested antibiotics and S. intermedius of 12.1% for both antibiotics.…”
Section: Resultsmentioning
confidence: 90%
“…The isolates used in this study were collected, identified, and tested for antibiotic susceptibility in the study conducted by Rodrigues and collaborators [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bacterial species are capable of spreading in the hospital environment, and according to Oliveira (2008) (Andrade et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent and reduce the risks of contamination, biosecurity measures must be implanted and followed. Measures such as the adoption of rules, secure methods that are appropriated to the maintenance of the health of patients, professionals, and visitors, which help prevent the dissemination of infectious agents, therefore decreasing the risk of developing a nosocomial infection, especially bacterial infections: Stenotrophomonas maltophilia, Klebsiella pneumoniae, Escherichia coli, Streptococcus pneumoniae, Haemophilus influenzae, Acinetobacter baumannii and Staphylococcus aureus, and they may present resistance to several antimicrobials (Zhong, 2020;Andrade, 2021).…”
Section: Introductionmentioning
confidence: 99%